Moving from the margins: Life histories on transforming the study of racism - Andersen, Margaret L; Zinn, Maxine Baca (California Stanford University press, 2024)
At a time when movements for racial justice are front and center in U.S. national politics, this book provides essential new understanding to the study of race, its influence on people's lives, and what we can do to address the persistent and foundational American problem of systemic racism. Knowledge about race and racism changes as social and historical conditions evolve, as different generations of scholars experience unique societal conditions, and as new voices from those who have previously been kept at the margins have challenged us to reconceive our thinking about race and ethnicity.
Keywords: Sociologists United States biography; Racism Study and teaching (Higher) United States; Sociologists